Retromuscular Sublay Technique for Ventral Hernia Repair - Rhemtulla, Irfan A.; Fischer, John P. (Seminars in Plastic Surgery, 2018)
Rives and Stoppa described the sublay technique of hernia repair more than half a century ago, but it took almost three decades to become truly appreciated and even longer for its full clinical potential and benefits to be realized. Modifications to the original operation have significantly improved surgical approaches, postsurgical outcomes, and quality of life. The retromuscular approach requires technical expertise and a firm grasp of the anatomy. With constant substitution of the terms sublay, retrorectus, retromuscular, preperitoneal, and Rives-Stoppa throughout the literature, the nuances need to be distinguished to appreciate the surgical planes encountered during the operation. This article explains the origin of the nomenclature while clarifying these terms, describing the technique, highlighting outcomes, and discussing future considerations.
Keywords: sublay; retrorectus; retromuscular; preperitoneal; Rives-Stoppa